Canada : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper for Canada presents comprehensive and broad-based analysis of the role of domestic and external shocks. Canada's economic history illustrates the important role played by external as well as domestic macroeconomic disturbances. Canada's economy slowed in 2001 because of the global slowdown, although by less than in many other countries. In 2003, the recovery has been interrupted by a series of shocks that moderated growth. Fluctuations in Canadian real GDP are explained by external and domestic cycles.